Enhancement of biohydrogen production by employing a packed-filter bioreactor (PFBR) utilizing sulfite-rich organic effluent obtained from a washing process of beverage manufactures. (June 2022) - Chu, Chen-Yeon; Zheng, Jin-Long; Bhuyar, Prakash
Abstract: Escalating necessity over exhausting fossil fuels needs an alternative source of energy. In this investigation, a packed-filter bioreactor was employed to generate hydrogen using sulfite wastewater as a substrate. The seed sludge was obtained from the sewage treatment plant. The results discovered that the substrate concentration was 10 g total sugar/L, the hydrogen content ranged from 36.3 to 29.18%, the hydrogen production rate (HPR) ranged from 20.8 to 6.50 L/L/d the sulfite concentration ranged from 20 to 80 mg. The wastewater's biohydrogen production rate declined when the sulfite concentration exceeded 40 mg/L. The hydrogen production rate in the packed-filter bioreactor (PFBR) using sulfite wastewater can stretch to 15.2 ± 0.41 L/L/d, Yield of 0.82 ± 0.01 mol H2 /mol hexose, cell concentration of 6.57 ± 0.21 g VSS/L when operating under 2.5 g total sugar/L, hydraulic retention time 0.25 h, despite the unfavorable sulfite. The PFBR can degrade organic matter in sulfite wastewater with a short hydraulic retention time and a high organic loading rate. In a nutshell, the findings of this research can be utilized to broaden the usage of gaseous bioenergy in the practical implementation of government sewerage. Graphical abstract: Image 1 Highlights: A packed-filter bioreactor was employed to generate bio-hydrogen. Optimization for biohydrogen production from beverage manufactures. The PFBR operates in sulfite wastewater with a low HRT and substrate conc. The PFBR can be employed in the actual gaseous bioenergy generation.